Enhanced electrochemical performance of Li2FeSiO4/C cathode materials by surface modification with AlPO4 nanosheets. (20th December 2016) - Qiu, Hailong; Yue, Huijuan; Zhang, Tong; Li, Tingting; Wang, Chunzhong; Chen, Gang; Wei, Yingjin; Zhang, Dong
Abstract: Lithium iron silicates (Li2 FeSiO4 ) are promising materials for use as cathodes because they may theoretically allow a two-electron exchange per formula unit. However, the high operating voltage (4.8 V vs. Li + /Li) may promote unwanted side-reactions between the cathode and electrolyte, causing serious capacity fading during cycling. In this report, Li2 FeSiO4 /C materials coated with AlPO4 nanosheets are successfully prepared to improve the electrochemical performance of the lithium iron silicates. The structure and morphology of the samples are characterized using XRD, SEM and TEM analysis. Compared with the pristine sample that has not been modified, the 2 wt.% AlPO4 -coated sample exhibits enhanced rate capability and cycling performance, especially at elevated-temperature. Additionally, the AlPO4 coating layer suppresses the stress of the volume change and prevents separation of the carbon layer from the host material during cycling.